2012
DOI: 10.1186/1742-2094-9-209
|View full text |Cite
|
Sign up to set email alerts
|

IgG glycan hydrolysis by EndoS inhibits experimental autoimmune encephalomyelitis

Abstract: Studies in experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis, have shown that B cells markedly influence the course of the disease, although whether their effects are protective or pathological is a matter of debate. EndoS hydrolysis of the IgG glycan has profound effects on IgG effector functions, such as complement activation and Fc receptor binding, suggesting that the enzyme could be used as an immunomodulatory therapeutic agent against IgG-mediated diseases. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Mechanistically, it is clear that these antibodies alone are not capable of initiating EAE in otherwise naïve animals. However, certain studies suggest that they may facilitate CNS damage and promote progression of ongoing EAE [Benkhoucha et al 2012]. More than 20 years ago, Schluesener and colleagues reported that intravenous administration of a monoclonal antibody against MOG enhanced CNS demyelination and induced fatal relapses in a rodent disease model [Schluesener et al 1987].…”
Section: B Cells As Precursors Of Antibody Secreting Plasma Cellsmentioning
confidence: 99%
“…Mechanistically, it is clear that these antibodies alone are not capable of initiating EAE in otherwise naïve animals. However, certain studies suggest that they may facilitate CNS damage and promote progression of ongoing EAE [Benkhoucha et al 2012]. More than 20 years ago, Schluesener and colleagues reported that intravenous administration of a monoclonal antibody against MOG enhanced CNS demyelination and induced fatal relapses in a rodent disease model [Schluesener et al 1987].…”
Section: B Cells As Precursors Of Antibody Secreting Plasma Cellsmentioning
confidence: 99%
“…Therefore, enzymes with activity on these glycans could be developed as pharmaceuticals against antibody mediated autoimmune diseases. Toward that end, EndoS has been successful as experimental treatment in a number of animal models of antibody mediated autoimmunity, including arthritis, systemic lupus erythematosus, multiple sclerosis, autoimmune kidney disease and autoimmune blistering skin diseases [20,22,[50][51][52][53][54][55][56]. This work, which is based on the functional similarities between EndoSd from SDSD and EndoS from S. pyogenes emphasize the close evolutionary relationship between the species and contributes to a deeper understanding of the biology of immune evasion by bacterial pathogens.…”
Section: Resultsmentioning
confidence: 89%
“…These include arthritis, systemic lupus erythematosus (SLE), autoimmune thrombocytopenia, autoimmune hemolysis, bullous skin disease, autoimmunity of the kidney, and multiple sclerosis. [95][96][97][98][99][100][101][102] Furthermore, it has recently been demonstrated that pathogenic antibodies from neuromyelitis optica can be transformed into potentially therapeutic antibodies by ex vivo treatment with EndoS. 103 Since the discovery of EndoS, several structurally or functionally related enzymes have been identified in other bacterial pathogens.…”
Section: Specific Immunoglobulin Glycan Hydrolasesmentioning
confidence: 99%